Sapiens : a brief history of humankind - Harari, Yuval N. (Harper, 2015)
"One hundred thousand years ago, at least six different species of humans inhabited Earth. Yet today there is only one--homo sapiens. What happened to the others? And what may happen to us? Most books about the history of humanity pursue either a historical or a biological approach, but Dr. Yuval Noah Harari breaks the mold with this highly original book that begins about 70,000 years ago with the appearance of modern cognition."--